GENOTOXIC EFFECT OF PESTICIDES ON HUMAN LEUKOCYTE CULTURE: A REVIEW - Mitra, Debanjana; Vg, Abilash (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Pesticides have long been in use in the agricultural fields, plantation firms, and also for household purposes. However, there are a considerable number of studies which prove the detrimental effects of the pesticides that include biochemical, histopathological, and genetic effects. The aim of this article is to present a review on the effects of pesticides on leukocytes which have been analyzed through various assays including chromosome analysis, cytokinesis-block micronuclei assay, comet assay, semen, and sperm analysis. The studies have shown organophosphates and carbamates to be the most potential sources of genotoxicity and the individuals exposed to these groups of pesticides are relatively much more prone to genotoxicity. Further investigation on molecular mechanism by which the pesticides affect the genome of cells needs to be carried out. Keywords: Pesticides, Genotoxicity, Chromosome analysis, Cytokinesis-block micronucleus cytome assay, Semen analysis.